Single-Wall Carbon Nanotubes Covalently Functionalized with Polylysine: Synthesis, Characterization and Analytical Applications for the Development of Electrochemical (Bio)Sensors - Gasnier, Aurelien (2014)
This work reports the synthesis of single-wall carbon nanotubes (SWCNT) covalently functionalized with polylysine (Plys) and the analytical performance of glassy carbon electrodes (GCE) modified with this material (GCE/SWCNT-Plys). The resulting electrodes showed an important decrease in the overvoltages for the oxidation of ascorbic acid, uric acid and hydrogen peroxide as well as for the reduction of hydrogen peroxide. The favorable interaction of glucose oxidase (GOx) with SWCNT-Plys allowed the sensitive and selective glucose biosensing at −0.100 V without any permselective membrane. The proposed sensor was challenged with different real samples without pretreatment showing an excellent correlation with the reported values.